INTEGRATING TAX FAIRNESS, GOVERNMENT MARKETING STRATEGY, AND INSTITUTIONAL TRUST: A MODERATED MEDIATION MODEL OF TAX COMPLIANCE IN INDONESIA - M. Gunawan Setyadi; Tino Feri Efendi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study examines the behavioral determinants of tax compliance by integrating perceived tax fairness, government marketing strategy, institutional trust, and perceived enforcement into a unified moderated mediation framework. Grounded in Equity Theory, the Slippery Slope Framework, and Government Marketing Theory, the research explores how fairness perceptions influence compliance both directly and indirectly through trust in tax authorities, while also assessing the moderating roles of public communication and enforcement mechanisms. A quantitative explanatory design was employed using survey data collected from 250 registered individual taxpayers in Bandung, Indonesia. Respondents were selected through purposive sampling based on active tax status and experience with electronic tax reporting systems. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate measurement validity, structural relationships, and moderation effects. The findings reveal that perceived tax fairness significantly enhances trust in tax authorities. Trust, in turn, exerts a strong positive effect on tax compliance, confirming its central mediating role. The direct effect of fairness on compliance becomes weaker when trust is included, indicating partial mediation. Government marketing strategy positively influences trust and strengthens the relationship between fairness and trust, highlighting the importance of transparent communication, public education, and fiscal storytelling. Meanwhile, perceived enforcement demonstrates a positive but comparatively weaker moderating effect on the trust–compliance relationship, suggesting that balanced power and legitimacy are essential for sustainable compliance. The study contributes theoretically by extending the Slippery Slope Framework through the incorporation of public marketing as a behavioral governance instrument. Practically, the findings underscore the strategic importance of fairness-based communication and consistent enforcement in fostering voluntary, trust-driven tax compliance in emerging economies. Keywords: Tax fairness; institutional trust; tax compliance; government marketing strategy; perceived enforcement